ANALISIS RISIKO KECELAKAAN KERJA METODE HIRA (HAZARD IDENTIFICATION AND RISK ASSESSMENT) DI PT. X - Wita Afnella; Tri Niswati Utami (Universitas Pahlawan, 2021)
The HIRA (Hazard Identification, Risk Assessment) method is a process of identifying hazards that occur in all company activities, then conducting a risk assessment of the hazards that occur. Introduction: Based on the initial survey conducted at PT. X, it was found that there were work accidents such as pinched hands, cuts, entanglement in processing machines which caused the risk of accidents. This research was conducted at PT.X in February-August 2021. Methods: This study used a descriptive qualitative method. This study analyzes the risk of work accidents using the HIRA (Hazard Identification, Risk Assessment) method which aims to identify hazards and conduct a risk assessment of these hazards. The research informants were 6 people consisting of 2 key informants and 4 main informants. Results: The results showed that there were 44 types of hazards from 8 work stations at PT. X. Among them, 16% have a small risk of harm (trivial), 38.6% have a tolerable risk, 34.1% have a moderate risk of harm, 4.5% have a substantial risk of harm, 6, 8% have an intolerable risk of harm. Conclusion: Risk analysis is a process by which hazards are identified and risks are estimated to assess the damage caused with the likelihood of damage occurring.